2008
DOI: 10.1086/525273
|View full text |Cite
|
Sign up to set email alerts
|

Mid‐Infrared Spectroscopy of Lensed Galaxies at 1 <z< 3: The Nature of Sources Near the MIPS Confusion Limit

Abstract: We present Spitzer IRS mid-infrared spectra for 15 gravitationally lensed, 24 mYselected galaxies, and combine the results with four additional very faint galaxies with IRS spectra in the literature. The median intrinsic 24 m flux density of the sample is 130 Jy, enabling a systematic survey of the spectral properties of the very faint 24 m sources that dominate the number counts of Spitzer cosmological surveys. Six of the 19 galaxy spectra (32%) show the strong mid-IR continuua expected of AGNs; X-ray detecti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
129
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 92 publications
(147 citation statements)
references
References 85 publications
(167 reference statements)
18
129
0
Order By: Relevance
“…This result is consistent with the earlier findings by various Spitzer observations (e.g., Papovich et al 2007;Rigby et al 2008). This also implies that these higher-redshift star-forming galaxies have a larger amount of colder dust compared to the local galaxies with similar infrared luminosities.…”
Section: Overview Of the Bullet Cluster Sdp Datasupporting
confidence: 94%
See 1 more Smart Citation
“…This result is consistent with the earlier findings by various Spitzer observations (e.g., Papovich et al 2007;Rigby et al 2008). This also implies that these higher-redshift star-forming galaxies have a larger amount of colder dust compared to the local galaxies with similar infrared luminosities.…”
Section: Overview Of the Bullet Cluster Sdp Datasupporting
confidence: 94%
“…However, the validity of all these Spitzer-based results rests on the assumption that the total infrared luminosities of high-redshift infrared galaxies can be estimated accurately by sampling their rest-frame mid-infrared emission (e.g., the MIPS 24 μm band samples the rest-frame 8 μm emission at z = 2). Indeed, some Spitzer results have already questioned this assumption, suggesting that the use of local galaxy spectral energy distribution (SED) templates may lead to overestimating the total infrared luminosities of high-redshift galaxies (e.g., Papovich et al 2007;Rigby et al 2008). Herschel will allow us to measure the total infrared luminosities of a large number of high-redshift galaxies directly for the first time.…”
Section: Introductionmentioning
confidence: 99%
“…Rigby et al 2008;Farrah et al 2008). On the one hand, Engelbracht et al (2008) find that the differences between the SEDs of local and z ∼ 2 ULIRGs are qualitatively consistent with a difference in metallicity of a factor 1.5-2.…”
Section: Introductionmentioning
confidence: 82%
“…They make use of observations of suppressed PAH emission in local LIRGs and ULIRGs (whereby heavy molecules are destroyed in the most dense star forming environments, e.g. Rigby et al, 2008;Díaz-Santos et al, 2010) to distinguish two modes of star formation where normal main sequence galaxies have IR8 values consistent with local LIRGs, whereby starbursts have elevated IR8 ratios, consistent with local ULIRGs. They find that ULIRGs at z ∼ 1−2 have IR8 ratios consistent with normal main sequence star forming galaxies and thus conclude that most Herschel-Pacs detected galaxies are not merger dominated.…”
Section: Mid-infrared Diagnosticsmentioning
confidence: 99%
“…The physical origins of DOGs mid-infrared emission could have been AGN-heating or bright PAH emission lines. Rigby et al (2008), Farrah et al (2008), Murphy (2009 and Takagi et al (2010) found the latter (note however that not all of these works explicitly use the DOG selection criterion, their samples overlap substantially). Indeed, the AGN fraction of DOGs (and similar z ∼ 2 BzKs) appears to be smaller than was originally anticipated ∼30% at S 24 < 1 mJy Alexander et al, 2011).…”
Section: Mid-infrared Spitzer-selected Populationsmentioning
confidence: 99%